2020
DOI: 10.1007/s10669-020-09773-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID, resilience, and the built environment

Abstract: This article provides a perspective on the reciprocal relationships between public and private sector resilience planning activities and the ongoing COVID responses in the U.S. Through the lens of the built environment, this article provides selected insights into how various disaster, organizational, and engineering resilience activities have likely positively shaped COVID responses within the healthcare sector. These positive influences are contextualized within extensive efforts within public health and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 43 publications
2
48
0
4
Order By: Relevance
“…These facilities are reliant on preexisting technological infrastructure, that is, site utilities, access to transport routes to maintain supply chain continuity, telecommunications support, and availability of installation sites ranging from community centers to sports stadiums and to open fields (Fang et al, 2020). Field hospital installations must be quickly Health Environments Research & Design Journal XX(X) constructible, cost-effective, and reduce capacity pressures on nearby conventional medical facilities (Keenan, 2020;Louri et al, 2020;Pucher et al, 2014;Zhou et al, 2020). The Fangcang shelter hospitals had the advantage of constructability on immediately available land parcels.…”
Section: Rapid Responsivenessmentioning
confidence: 99%
“…These facilities are reliant on preexisting technological infrastructure, that is, site utilities, access to transport routes to maintain supply chain continuity, telecommunications support, and availability of installation sites ranging from community centers to sports stadiums and to open fields (Fang et al, 2020). Field hospital installations must be quickly Health Environments Research & Design Journal XX(X) constructible, cost-effective, and reduce capacity pressures on nearby conventional medical facilities (Keenan, 2020;Louri et al, 2020;Pucher et al, 2014;Zhou et al, 2020). The Fangcang shelter hospitals had the advantage of constructability on immediately available land parcels.…”
Section: Rapid Responsivenessmentioning
confidence: 99%
“…It is reported that although the country's GDP in the first quarter of 2020 fell by 6.8%, the GDP in the second quarter increased by 3.2% It shows that the economic growth rate has changed from negative to positive, implying that the overall economy has shown a rapid recovery (National Bureau of Statistics of China, 2020). During disruptions such as the COVID-19 pandemic, the resilience of commercial organizations becomes a critical issue to investigate [8,9]. The systematic shock of the COVID-19 pandemic and the later recovery in China make the country an appropriate context for research on organizational resilience which is defined as a system's latent ability to endure adversity as well as to recover after a shock [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since various dimensions of this problem is still unknown (i.e., we do not have a quantitative metric to evaluate the risk, and we clearly are not prepared to face it), the authors implore governments to allocate additional financial resources to multi-hazard risk research, paving the way for a safer, less uncertain future. While the COVID-19 pandemic and all its consequences were unfortunate for the society, some researchers note that it might yield positive impacts for future resilience design, plans, and politics within built environments [ 65 , 80 ]. Last but not least, the author believes that anyone in any position should contribute (to the extent possible) to improve the knowledge related to the COVID-19 outbreak, and as Haas [ 81 ] truly said: “ Risk analysts and risk analysis researchers should not be shy about contributing our skills to important policy developments during this crisis.…”
Section: Discussionmentioning
confidence: 99%